Dielectric properties of chicken and fish muscle treated with microbial transglutaminase - Basaran, Pervin; Basaran-Akgul, Nese; Rasco, Barbara A. (Food chemistry, 2010)
Transglutaminase (MTGase) initiates the formation of covalent bonds between glutamine and lysine residues in proteins. Adding MTGase can improve the thermal stability of meat proteins, imparting desirable properties to reconstructed products during heating. In this study, the dielectric constant and loss factor of MTGase (0.5%)-treated chicken, salmon and trout muscle were determined and compared with untreated muscle at RF (27 and 40MHz) and MW (433, 915, and 1800MHz) frequencies from 20 to 130°C. The MTGase-treated chicken muscle tended to have higher dielectric constant and loss values at RF frequencies at all temperatures tested. At MW frequencies, the dielectric constants were similar between the MTGase-treated chicken muscle and the control, but the dielectric loss was higher for the MTGase-treated tissue. Similar trends were observed for salmon or trout tissue for dielectric constant; however, at RF frequencies, the dielectric loss factor for MTGase-treated fish was not consistently higher than that of the control. Dielectric loss factors were higher for salmon or trout at RF frequencies than for chicken muscle at the same temperature. The addition of MTGase promotes cross-linking and stronger gel formation for RF and MW treatment.
Gesehen am 06.12.2022